RETRACTED: Human and Environmental Dangers Posed by Ongoing Global Tropospheric Aerosolized Particulates for Weather Modification - Herndon, J. Marvin (Frontiers in Public Health, 2016)
Background U.S. military perception of nuclear warfare led to countless unethical nuclear experiments performed on unsuspecting individuals without their informed consent. As evidenced here, subsequent perception of weather warfare has led to exposing millions of unsuspecting individuals to toxic coal fly ash with no public disclosure, no informed consent, and no health warnings. Methods Three methods were used: (1) comparison of eight elements analyzed in rainwater samples, thought to have leached from aerosolized coal fly ash, with corresponding coal fly ash laboratory leachate; (2) comparison of 14 elements analyzed in air filter dust with corresponding elements in coal fly ash; and (3) comparison of 23 elements analyzed in fibrous mesh found after snow melted with corresponding elements in coal fly ash. Results The rainwater element ratios show that the aerial particulate matter has essentially the same water-leach characteristics as coal fly ash. The air filter dust element ratios occur in the same range of compositions as coal fly ash, as do element ratios in fibrous mesh found on grass after snow melted. The fibrous mesh provides an inferred direct connection with the aerosolizing jet aircraft via coal fly ash association with the jet combustion environment. Conclusion Strong evidence for the correctness of the hypothesis: coal fly ash is likely the aerosolized particulate emplaced in the troposphere for geoengineering, weather modification, and/or climate alteration purposes. The documented public health associations for ≤2.5 μm particulate pollution are also applicable to aerosolized coal fly ash. The ability of coal fly ash to release aluminum in a chemically mobile form upon exposure to water or body moisture has potentially grave human and environmental consequences over a broad spectrum, including implications for neurological diseases and biota debilitation. The ability of coal fly ash to release heavy metals and radioactive elements upon exposure to body moisture has potentially grave human health implications including cancer, cardiovascular disease, diabetes, respiratory diseases, reduced male fertility, and stroke. The fibrous mesh data admit the possibility of environmentally disastrous formation of methylmercury and ozone-depleting chlorinated-fluorinated hydrocarbons in jet exhaust. Geophysical implications include atmospheric warming and rainfall retardation.